The Translational Potential of Microglia and Monocyte-Derived Macrophages in Ischemic Stroke - Wicks, Elizabeth E.; Ran, Kathleen R.; Kim, Jennifer E.; Xu, Risheng; Lee, Ryan P.; Jackson, Christopher M. (Frontiers in Immunology, 2022)
The immune response to ischemic stroke is an area of study that is at the forefront of stroke research and presents promising new avenues for treatment development. Upon cerebral vessel occlusion, the innate immune system is activated by danger-associated molecular signals from stressed and dying neurons. Microglia, an immune cell population within the central nervous system which phagocytose cell debris and modulate the immune response via cytokine signaling, are the first cell population to become activated. Soon after, monocytes arrive from the peripheral immune system, differentiate into macrophages, and further aid in the immune response. Upon activation, both microglia and monocyte-derived macrophages are capable of polarizing into phenotypes which can either promote or attenuate the inflammatory response. Phenotypes which promote the inflammatory response are hypothesized to increase neuronal damage and impair recovery of neuronal function during the later phases of ischemic stroke. Therefore, modulating neuroimmune cells to adopt an anti-inflammatory response post ischemic stroke is an area of current research interest and potential treatment development. In this review, we outline the biology of microglia and monocyte-derived macrophages, further explain their roles in the acute, subacute, and chronic stages of ischemic stroke, and highlight current treatment development efforts which target these cells in the context of ischemic stroke.